Pengembangan Multimedia Interaktif Berbasis TPACK pada Mata Pelajaran Informatika Kelas VII di SMP - Anisya, Anisya; Anugrah, Septriyan; Hendri, Nofri; Masnur, Alkadri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The research aims to develop framework-based interactive multimedia on Techonogical Pedagogical Content Knowledge in informatics subjects at the junior high school level. The type of research used is the Research and Development (R&D) method with a development model (Analysis, Design, Development, Implementation, Evaluation). At the development stage, an analysis of needs in the field, storyboard design, media development using the articulate storyline application, and product trials were carried out to students. The instruments used in the study consist of observations, questionnaires, and learning outcome tests with the aim of determining the practicality and effectiveness of the products developed. The validation test data from the material aspect obtained a score of 4.00 with the criterion of